Clustering of non-communicable diseases risk factors in Bangladeshi adults: An analysis of STEPS survey 2013. (December 2015) - Zaman, M.; Bhuiyan, Mahfuzur; Karim, Md.; MoniruzZaman,; Rahman, Md.; Akanda, Abdul; Fernando, Thushara
Abstract Background Non-communicable diseases (NCDs) have already become major killers in Bangladesh. Once NCDs are developed, they become chronic health and economic problems. Their primary prevention is linked to their common risk factors. This study was conducted to determine the prevalence of NCD risk factors with a focus on their clustering in Bangladeshi adults. Methods This nationally representative study was done in 4, 073 (1, 812 men and 2, 261 women) adults aged 25 years or older selected from rural and urban households. Multistage cluster sampling design was used. Selected variables were in line with steps I and II of WHO stepwise surveillance except alcohol. Results Forty-four percent used tobacco in any form. Almost 93 % did not consume adequate fruit and vegetables (5 servings or more). Thirty eight percent had low physical activity level (<600 MET-minutes/week). One-quarter (26 %) were overweight (body mass index > =25 kg/m^2). Twenty-one percent had hypertension (blood pressure > =140/90 mmHg or medication) and about 5 % had documented diabetes. Upon examination of risk factor clustering, we observed that 38 % had at least three risk factors. After this threshold, clustering suddenly dropped down to a fairly low level. Using this threshold as a cut-off, clustering of risk factors was associated with age, male gender, urban residence, educational levels and quality of house in multivariate analysis. Conclusion Prevalence of NCD risk factors is fairly high in Bangladeshi adults with a tendency of clustering. If a risk factor such as hypertension is detected, a closer look for other risk factors has to be given in both at clinical and public health settings. Clustering raises risk by more than a summation of risk factors. Our findings, therefore, suggest that Bangladesh could expect a significant increase in NCDs in near future.